(untitled) (The Review of Diabetic Studies, 2024)
Background: Healthcare-associated infections (HAIs) remain a major cause of morbidity and mortality in neonatal intensive care units (NICUs), particularly among preterm and very low birth weight infants. Immature immune systems, frequent invasive procedures, prolonged device use, and exposure to multidrug-resistant organisms increase susceptibility, especially in low- and middle-income countries where resource limitations further exacerbate infection risk. Methods: This narrative review synthesizes peer-reviewed literature published between 2010 and 2026 examining the epidemiology, pathophysiology, and prevention of HAIs in NICUs. Databases were reviewed for studies addressing hand hygiene, device-associated care bundles, environmental interventions, antimicrobial stewardship, surveillance systems, educational programs, and emerging technologies. Evidence from both high-income and resource-limited settings was included to capture global perspectives. Results: Bloodstream infections were identified as the most prevalent HAIs in NICUs, followed by ventilator-associated pneumonia and fungal infections. Multimodal prevention strategies, particularly central line and ventilator care bundles, were associated with 50–70% reductions in device-associated infections. Hand hygiene interventions improved compliance to over 80% and reduced infection rates by up to 50%. Surveillance, staff education, and antimicrobial stewardship programs further contributed to sustained improvements. Emerging innovations such as rapid diagnostics, artificial intelligence–based monitoring, probiotics, and antimicrobial coatings show promise but require further validation. Conclusions: Effective prevention of HAIs in NICUs requires integrated, evidence-based, and context-adapted multimodal strategies. Strengthening policy support, implementation science, and equitable resource allocation is essential to sustain infection reductions and improve neonatal outcomes globally.